(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This paper studies the syntactic explicitation of adversative logical relations in literary translation from Chinese to Spanish. Taking four modern Chinese literary works and their respective Spanish translated texts for example, we use a corpus-based quantitative method to describe the translation of adversative sentences and the use of Spanish adversative conjunctions. The results support the hypothesis of the explicitation of the adversative relations. The qualitative approach is further applied to explain the motivations of the explicitation. This study shows that the main factors that affect the degree of explicitness in the target text include: (1) the inherent characteristics of the translation, (2) the differences between Chinese and Spanish in the expression of logical relationships, (3) the use of adversative conjunctions in the source text, (4) the subjectivity of translator, such as attention given to target readers, the adopted translation strategy and methods.